Recent Updates in the Pharmacological Management of Sepsis and Septic Shock: A Systematic Review Focused on Fluid Resuscitation, Vasopressors, and Corticosteroids. Issue 4 (April 2019) - Allen, John M.; Feild, Carinda; Shoulders, Bethany R.; Voils, Stacy A.
Objective: Describe recent developments in the pharmacological management of sepsis and septic shock, focusing on fluid resuscitation, vasopressors, and corticosteroids. Data Sources: A literature search limited to randomized controlled trials written in the English language reporting mortality and other clinically relevant outcomes that were published from July 1, 2016, to August 31, 2018, in patients aged ≥ 18 years. Titles and abstracts were reviewed for relevance. References for pertinent review articles were also reviewed. Study Selection and Data Extraction: Relevant randomized controlled trials conducted in patients meeting the pre-defined inclusion criteria were considered for inclusion. Data Synthesis: From an initial search that identified 147 studies, 14 original research studies met inclusion criteria and were included in this review. Risk of bias (ROB) was assessed using the Revised Cochrane ROB assessment tool, with most included studies having a low ROB. Relevance to Patient Care and Clinical Practice: Sepsis and septic shock pose a significant burden on public health. Despite advances in our understanding of sepsis, mortality remains unacceptably high. Recent developments in the pharmacological management of septic shock have focused on determining optimal composition and dosage of fluid resuscitation, enhanced use of vasopressor therapy, and clarifying the role of corticosteroids. This systematic review will provide recommendations for application to practice focusing on recent research on these topics. Conclusions: Although recent developments in the pharmacological management of sepsis are encouraging, clinicians must be keen to utilize patient-specific factors to guide therapy and continue to strive to address the remaining unanswered questions.